Pengaruh Latihan Jump Box Terhadap Hasil Kemampuan Three Point Shoot Pemain Bolabasket - Sartika, Dwi; Bayu, Wahyu Indra; Aryanti, Silvi (Jurnal MensSana, 2023)
This study aims to determine the effect of jump box training on the results of three-point shoots for extracurricular basketball students at SMA Negeri 1 Martapura. The method used in this research is an experiment. The research design used was the One Group Pretest-Posttest Design. This sample was taken using a total population sampling technique with a total sample of 39 students. The research instrument was the three-point shoot test. From the results of data management and analysis using the data normality test and hypothesis testing with the T-test formula, jump box training has an effect on increasing the results of three-point shoots in basketball games. This can be seen from the results of data analysis through the calculation of the t-test formula with the criteria t count is greater than t table (13.730 ˃ 1.70) with a confidence level of 0.95 (α = 0.05) and the number of samples (N = 30). Jump box training can have an effect on increasing the results of three-point shoots for basketball extracurricular students at SMA Negeri 1 Martapura.